No Use: Nuclear Weapons and U.S. National Security - Nichols, Thomas (Haney Foundation Series, 2013)
For more than forty years, the United States has maintained a public commitment to nuclear disarmament, and every president from Ronald Reagan to Barack Obama has gradually reduced the size of America's nuclear forces. Yet even now, over two decades after the end of the Cold War, the United States maintains a huge nuclear arsenal on high alert and ready for war. The Americans, like the Russians, the Chinese, and other major nuclear powers, continue to retain a deep faith in the political and military value of nuclear force, and this belief remains enshrined at the center of U.S. defense policy regardless of the radical changes that have taken place in international politics.In No Use, national security scholar Thomas M. Nichols offers a lucid, accessible reexamination of the role of nuclear weapons and their prominence in U.S. security strategy. Nichols explains why strategies built for the Cold War have survived into the twenty-first century, and he illustrates how America's nearly unshakable belief in the utility of nuclear arms has hindered U.S. and international attempts to slow the nuclear programs of volatile regimes in North Korea and Iran. From a solid historical foundation, Nichols makes the compelling argument that to end the danger of worldwide nuclear holocaust, the United States must take the lead in abandoning unrealistic threats of nuclear force and then create a new and more stable approach to deterrence for the twenty-first century.